SOCIAL AND METHODOLOGICAL REFLEXES IN THE EVOLUTION OF NEUROLOGY AND THE CURRENT SITUATION OF THIS MEDICAL FIELD IN BRAZIL - Steven Philippart, Kevin; Sayuri Shiraishi, Leticia; Domingos Ribeiro, Lucas; Ventura Tauyr, Luciana; Tadeu Guardia Júnior, Marcos; Espirito Santo Campos, Nathalia (Health and Society, 2021)
The objective of this systematic review article is to analyze the evolution of neurology in the face of studies throughout the world until the separation of the organic body and the mental body, formalizing a new vision of medical treatment in neurology and also update the current situation of this study area of modern medicine in Brazil. The methodology used was the search for articles, books and data archives that reported how this evolution occurred, descriptively and historically. And the conclusion drawn from the present review was that neurology and psychiatry are very close areas, and the progress in recognizing the patient as a whole in medical treating is closely related to these two medical areas.